Travelers and Intellectuals in Perspective. Modernities and Catholic Cultures in Twentieth-century Argentina - Zanca, Jos´é (Anuario de Historia de América Latina, 2025)
The aim of this paper is to describe and analyze a set of visits by prominent religious figures throughout the twentieth century in Argentina, examining their impact on Catholic culture. The experience of the trip brings together different and very varied instances, revealing for the study of social and human sciences. From literature to the materiality of transfers, including the study of networks and the impact, limited or perennial, of a guest. In the cases listed in this paper, we intend to analyze what kind of effects these visits had on Argentine Catholic culture throughout much of the twentieth century, with the conviction that this window can show us some characteristics that, otherwise, we could not observe. As a hypothesis, we maintain the conflictive character of the Catholic cultural field, a territory in which, beyond the episcopal discourse on verticality and obedience, an almost permanent dispute of power for the monopoly of truth can be observed.
Keywords: Cultural Visits; Catholicism; Catholic Church; Secularization.